2017
DOI: 10.1111/1462-2920.13722
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid‐mediated resistance to cephalosporins and quinolones in Escherichia coli from American crows in the USA

Abstract: American crow (Corvus brachyrhynchos) faeces were tested for Escherichia coli with plasmid-mediated quinolone resistance (PMQR), extended-spectrum beta-lactamases (ESBL) and AmpC beta-lactamases. A total of 590 faecal samples were collected at four roosting sites in the USA and cultivated on selective media. Pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST) were performed to assess clonality. Transferability of resistance genes was studied using conjugation and transformation bioas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
(99 reference statements)
1
13
0
Order By: Relevance
“…E. coli , which lives as a harmless commensal in the gut of all animal and birds, has proved to be not only an indicator of fecal coliform but also of antibiotic resistance present in the environment (van Den Bogaard et al, 2000; Dolejská et al, 2009; Guenther et al, 2011; Jamborova et al, 2015, 2018). From the United States, only one study investigating antibiotic resistance in E. coli in crows has been reported (Jamborova et al, 2017). In this study, which was a survey from four different states, 13% ( n = 590) of E. coli from American crows ( Corvus brachyrhyncos ) possessed AmpC and ESBL phenotypes, while 15% ( n = 590) were resistant to Ciprofloxacin (Jamborova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…E. coli , which lives as a harmless commensal in the gut of all animal and birds, has proved to be not only an indicator of fecal coliform but also of antibiotic resistance present in the environment (van Den Bogaard et al, 2000; Dolejská et al, 2009; Guenther et al, 2011; Jamborova et al, 2015, 2018). From the United States, only one study investigating antibiotic resistance in E. coli in crows has been reported (Jamborova et al, 2017). In this study, which was a survey from four different states, 13% ( n = 590) of E. coli from American crows ( Corvus brachyrhyncos ) possessed AmpC and ESBL phenotypes, while 15% ( n = 590) were resistant to Ciprofloxacin (Jamborova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From the United States, only one study investigating antibiotic resistance in E. coli in crows has been reported (Jamborova et al, 2017). In this study, which was a survey from four different states, 13% ( n = 590) of E. coli from American crows ( Corvus brachyrhyncos ) possessed AmpC and ESBL phenotypes, while 15% ( n = 590) were resistant to Ciprofloxacin (Jamborova et al, 2017). Two other studies reported on vancomycin resistant enterococci shed by crows in United States (Oravcova et al, 2014; Roberts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In winter, crows aggregate in large nocturnal roosts (sometimes .10,000 birds; Hinton et al 2015), often in areas of high human density and activity (Gorenzel and Salmon 1995, Hinton et al 2015. Crows are of particular concern with respect to disease transmission because they are common urban and suburban birds in North America (McGowan 2001) that can harbor numerous pathogens important to humans, domestic animals, and wildlife, including West Nile virus (Wheeler et al 2014, Hinton et al 2015, Campylobacter jejuni (Weis et al 2016, Taff and, and other pathogens (Miller et al 2010, Halová et al 2014, Freund et al 2016, Jamborova et al 2017, Townsend et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…coli MT102 is resistant to sodium azide, rifampin, and streptomycin due to missense mutations in the secA (3), rpoB (4), and rpsL (5) genes, respectively. This strain has been used in several studies characterizing mobile genetic elements carrying antimicrobial genes (68) and studies requiring a plasmid-free host (9, 10). E.…”
Section: Announcementmentioning
confidence: 99%